A Demonstration of a Versatile Low-order Wavefront Sensor Tested on Multiple Coronographs. (28th July 2017) - Singh, Garima; Lozi, Julien; Jovanovic, Nemanja; Guyon, Olivier; Baudoz, Pierre; Martinache, Frantz; Kudo, Tomoyuki
Abstract: Detecting faint companions in close proximity to stars is one of the major goals of current/planned ground- and space-based high-contrast imaging instruments. High-performance coronagraphs can suppress the diffraction features and gain access to companions at small angular separation. However, the uncontrolled pointing errors degrade the coronagraphic performance by leaking starlight around the coronagraphic focal-plane mask, preventing the detection of companions at small separations. A Lyot-stop low-order wavefront sensor (LLOWFS) was therefore introduced to calibrate and measure these aberrations for focal-plane phase mask coronagraphs. This sensor quantifies the variations in wavefront error decomposed into a few Zernike modes by reimaging the diffracted starlight rejected by a reflective Lyot stop. The technique was tested with several coronagraphs on the Subaru Coronagraphic Extreme Adaptive Optics (SCExAO) system at the Subaru Telescope. The wavefront was decomposed into 15 and 35 Zernike modes with an occulting and focal-plane phase mask coronagraph, respectively, which were used to drive a closed-loop correction in the laboratory. Using a 2000-actuator deformable mirror, a closed-loop pointing stability between 10 −3 –10 −4 λ / D was achieved in the laboratory in H-band, with sub nanometer residuals for the other Zernike modes (Noll index > 4 ). On-sky, the low-order control of 10+ Zernike modes for the phase-induced amplitude apodization and the vector vortex coronagraphs was demonstrated, with a closed-loop pointing stability of 10 − 4 λ / D under good seeing and 10 − 3 λ / D under moderate seeing conditions readily achievable.